UJI VALIDITAS ISI MODUL â€œFINGER PAINTINGâ€ UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS SEBAGAI PERSIAPAN KEMANDIRIAN MENGGOSOK GIGI ANAK DOWN SYNDROME DI SLB SRI SOEDEWI: CONTENT VALIDITY OF THE â€œFINGER PAINTINGâ€ MODULE TO ENCHANE FINE MOTOR SKILLS AS A PREPARATION FOR THE INDEPENDENCE OF TOOTBRUSHING FOR CHILDREN WITH DOWN SYNDROME AT SLB SRI SOEDEWI - Sayyidatina Salsabila Putri; Marlita Andhika Rahman; Annisa Andriani (Jurnal Psikologi Jambi, 2023)
ABSTRACT Introduction The activity of brushing teeth is necessary to maintain dental and oral hygiene. This is a crucial matter for all individuals, including those with down syndrome. During tooth brushing, fine motor skills such as finger dexterity and hand flexibility are required. Obstacles in fine motor aspects in children with down syndrome can lead to difficulties in performing such activities. Therefore, efforts are needed to stimulate fine motor skills, one of which is by providing activities like finger painting. This is the reason behind the development of the "Finger Painting" module to enhance fine motor skills as a preparation for tooth brushing for children with down syndrome at SLB Sri Soedewi. Objective To determine the content validity of the "Finger Painting" module in improving fine motor skills as preparation for the independence of tooth brushing for children with down syndrome at SLB Sri Soedewi. Method This research was a quantitative research with the type of module content validity test using Aiken's V as an analytical technique. The module was assesed by one clinical psychologist validator, one educational psychologist validator, and one validator from the SLB teacher. Results This research shows that the results of the content validation of the module range from a score of 0.83 to 0.92. The results of the validation of the interrater reliability sheet on thooth brushing behavior consist of 10 items with scores ranging from 0.83 to 1.00. Three items scored 0.75, and one item scored 0.5. Based on the results of the content validity test, the "Finger Painting" module is considered valid through a content validity test and has been improved based on the suggestions provided by the validators. Conclusion The "Finger Painting" module for enhancing fine motor skills as preparation for the independence of tooth brushing for children with down syndrome can be concluded as a valid module through a content validity test. Keywords: Content validity test, module, finger painting, fine motor skills, tooth brushing, children with down syndrome. ABSTRAK Pendahuluan Aktivitas menggosok gigi diperlukan untuk menjaga kebersihan gigi dan mulut, hal ini merupakan suatu hal yang penting bagi semua kalangan begitupun bagi anak down syndrome. Saat menggosok gigi diperlukan keterampilan motorik halus seperti kelenturan jari dan keluwesan tangan. Hambatan pada aspek motorik halus anak down syndrome dapat mengakibatkan kesulitan dalam melakukan aktivitas tersebut, sehingga perlu usaha menstimulasi kemampuan motorik halus. Salah satunya dengan memberikan aktivitas finger painting. Alasan inilah yang melatarbelakangi penyusunan modul â€œfinger paintingâ€ untuk meningkatkan kemampuan motorik halus sebagai persiapan menggosok gigi anak down syndrome di SLB Sri Soedewi. Tujuan Mengetahui uji validitas isi modul â€œfinger paintingâ€ untuk meningkatkan kemampuan motorik halus sebagai persiapan kemandirian menggosok gigi anak down syndrome di SLB Sri Soedewi. Metode Penelitian ini adalah kuantitatif dengan jenis uji validitas isi modul yang menggunakan Aikenâ€™V sebagai teknik analisis. Modul ini dinilai oleh satu validator psikolog bidang klinis, satu validator psikolog bidang pendidikan dan satu validator dari Guru SLB. Hasil Penelitian ini menunjukkan hasil validasi isi modul didapat bergerak dari rentang skor 0,83 hingga 0,92. Hasil validasi lembar interrater reliability perilaku menggosok gigi terdapat 10 item dengan skor rentang 0,83 hingga 1,00; 3 item memiliki skor 0,75; dan 1 item dengan skor 0,5. Berdasarkan hasil uji validitas isi, modul finger painting adalah modul yang valid melalui uji validitas isi, serta diperbaiki dengan saran perbaikan dari para validator. Kesimpulan Modul finger painting untuk meningkatkan motorik halus sebagai persiapan kemandirian menggosok gigi anak down syndrome dapat disimpulkan sebagai modul yang valid melalui uji validitas isi. Kata kunci: Uji validitas isi, modul, finger painting, kemampuan motorik halus, menggosok gigi, anak down syndrome.